Demographics and outcomes of acute type A aortic dissection in young adults in southeastern China: impact of syndromic heritable thoracic aortic disease - Xin-fan Lin; Hang-qi Gao; Qing-song Wu; Yu-ling Xie; Liang-wan Chen; Lin-feng Xie (Annals of Medicine)
Background This study aimed to investigate the demographics and to evaluate long-term outcomes of acute type A aortic dissection (ATAAD) in surgically treated patients ≤40 years in China.Methods This study included patients aged ≤40 with ATAAD who underwent surgical treatment at our institution between 2015 and 2019. The patients were categorized into groups according to heritable thoracic aortic disease (HTAD) presence or absence. The primary outcomes were in-hospital and late mortality, and aortic-related re-intervention.Results Our cohort included 141 patients aged ≤ 40, representing 14.6% of all patients with ATAAD treated during the same period. 35.5% (50 of 141) of these cases were associated with HTAD. Among them, only 16.0% were aware of their condition prior to the occurrence of ATAAD. Most patients underwent extensive arch procedures and in-hospital mortality rate of patients was 14.2%, which was higher in the HTAD group than in the non-HTAD group (20.0% vs. 11.0%, p = .142). The overall 7-year survival was 80.0%. Twenty patients required late aortic reoperations, with emergency surgeries accounting for 45% of the cases. The incidence of reoperation was significantly higher in the HTAD group than that in the non-HTAD group (p = .03). In addition, the late aortic reoperation remained a risk factor for long-term survival after adjusting for clinical factors.Conclusions The prevalence of HTAD is high in the cohort of younger patients with ATAAD. HTAD is associated with high rates of in-hospital mortality and late reoperation. Extensive primary aortic repair is safe and has long-term benefits in young patients with ATAAD. Regular imaging assessment of the thoracoabdominal aorta after surgery is imperative for improving the long-term prognosis.